2015
DOI: 10.1007/s10620-015-3658-0
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the J-Tip Guidewire for Selective Biliary Cannulation Compared to Conventional Guidewires (The JANGLE Study)

Abstract: The biliary cannulation rate of the J-tip guidewire was not significantly different from those of standard guidewires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
(60 reference statements)
0
14
0
Order By: Relevance
“…No difference in the biliary cannulation success rate or PEP incidence was found when 0.035-inch straight and angled-tipped guidewires were compared; the cannulation time was significantly shorter with the angled guidewire [34]. A recent RCT [35] compared angled and J-tipped guidewires, but the success rates for cannulation and the PEP incidence were similar. Hydrophilic-tipped guidewires are commonly used for biliary cannulation because of the reduced friction and good pushability.…”
Section: Does Success Of Biliary Cannulation Depend On the Type Of Gumentioning
confidence: 96%
“…No difference in the biliary cannulation success rate or PEP incidence was found when 0.035-inch straight and angled-tipped guidewires were compared; the cannulation time was significantly shorter with the angled guidewire [34]. A recent RCT [35] compared angled and J-tipped guidewires, but the success rates for cannulation and the PEP incidence were similar. Hydrophilic-tipped guidewires are commonly used for biliary cannulation because of the reduced friction and good pushability.…”
Section: Does Success Of Biliary Cannulation Depend On the Type Of Gumentioning
confidence: 96%
“…In recent years, J-tipped GWs to be used for luminal passage and stricture penetration have been developed and reported to be beneficial in selective biliary cannulation. Although the J-shaped tip is considered to be more suitable for pancreatic intervention owing to the low risks of damaging the pancreatic duct and wrong insertion into a branch duct, the utility and safety of J-shaped tip GW in pancreatic intervention had not previously been examined [12]. Here, the initial procedure success rate with the small J-tipped GW was significantly higher than that with the angle-tipped GW.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, J-tipped GW designed for improving luminal passage has been developed and reported to be beneficial in selective biliary cannulations [12, 13]. Although J-tipped GW was not applicable to pancreatic duct endoscopic intervention due to its large tip radius, the newly developed small J-tipped GW with a smaller loop has enabled pancreatic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Various procedural techniques intended to minimize the risk for the development of PEP have been assessed, but only GWC and prophylactic PD stenting have proved somewhat effective 10 . Omuta et al found that a J-shaped guidewire facilitated selective biliary cannulation 11 , but Tsuchiya et al demonstrated, in a prospective multicenter controlled study, that the J-tip guidewire was not significantly different from other guidewires in regard to rates of CBD cannulation 12 . Most published studies comparing the effectiveness of GWC and CC have shown divergent results for the two techniques in both preventing PEP and increasing the biliary cannulation rate 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Most nonrandomized and randomized studies have compared the effectiveness of guidewire-assisted cannulation (GWC) with that of contrast-assisted cannulation (CC) for the prevention of PEP but are restricted to low risk patients, and the results so far are conflicting 9 10 11 12 13 14 15 16 17 18 .…”
Section: Introductionmentioning
confidence: 99%